Different ways to forget: Electrophysiological mechanisms underlying item-method directed forgetting of angry and neutral faces - Kissler, Johanna; Hauswald, Anne (Frontiers in Behavioral Neuroscience, 2022)
Emotional stimuli, including faces, receive preferential processing and are consequently better remembered than neutral stimuli. Therefore, they may also be more resistant to intentional forgetting. The present study investigates the behavioural and electrophysiological consequences of instructions to selectively remember or forget angry and neutral faces. In an item-method directed forgetting experiment, angry and neutral faces were randomly presented to 25 student participants (4 males). Each face was followed by an instruction to either forget or remember it and the participants’ EEG was recorded. Later, recognition memory was unexpectedly tested for all items. Behaviourally, both hit and false alarm rates were higher for angry faces than for neutral faces. Directed forgetting occurred for neutral and angry faces as reflected in a reduction of both recognition accuracy and response bias. Event-related potentials revealed a larger late positive potential (LPP, 450 – 700 ms) for angry than for neutral faces during face presentation and, in line with selective rehearsal of remember items, a larger LPP following remember than forget cues. Forget cues generally elicited a larger frontal N2 (280 – 400 ms) than remember cues, in line with the forget instruction eliciting conflict monitoring and inhibition. Selectively following angry faces, a larger cue-evoked P2 (180 – 280 ms) was observed. Notably, forget cues following angry faces elicited a larger late frontal positivity (450 - 700 ms) potentially signalling conflict resolution. Thus, whereas both angry and neutral faces are subject to directed forgetting, on a neural level, different underlie the effect. While directed forgetting for neutral faces may be achieved primarily by selective rehearsal, particularly directed forgetting of angry faces involves an additional late frontal positivity, likely reflecting higher cognitive demands imposed by forgetting angry faces.